2009
DOI: 10.1128/aac.00113-09
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Differential Interactions of Quinazolinedione PD 0305970 and Quinolones with Gyrase and Topoisomerase IV

Abstract: Quinazoline-2,4-diones, such as PD 0305970, are new DNA gyrase and topoisomerase IV (topo IV) inhibitors with potent activity against gram-positive pathogens, including quinolone-resistant isolates. The mechanistic basis of dione activity vis-à-vis quinolones is not understood. We present evidence for Streptococcus pneumoniae gyrase and topo IV that PD 0305970 and quinolones interact differently with the enzyme breakage-reunion and Toprim domains, DNA, and Mg 2؉ -four components that are juxtaposed in the topo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 60 publications
6
85
0
Order By: Relevance
“…In several other species, quinazolinediones containing a 3′-(aminomethyl) pyrrolidinyl [3′-(AM)P] (or a related) group at C7 maintain activity against enzymes containing mutations that disrupt the water-metal ion bridge by forming binding interactions primarily through the C7 substituent (20,21,32,(38)(39)(40)(41)(42). As seen in Fig.…”
Section: D94gmentioning
confidence: 90%
“…In several other species, quinazolinediones containing a 3′-(aminomethyl) pyrrolidinyl [3′-(AM)P] (or a related) group at C7 maintain activity against enzymes containing mutations that disrupt the water-metal ion bridge by forming binding interactions primarily through the C7 substituent (20,21,32,(38)(39)(40)(41)(42). As seen in Fig.…”
Section: D94gmentioning
confidence: 90%
“…Recent work from Fisher's laboratory, using selection of stepwise mutations, confirmed that the primary target of diones is GyrB, with secondary mutations in ParE. Furthermore, it was shown that dione inhibition leads to double-stranded DNA breakage (288). Thus, it appears that while mutations arise in the ATPase subunit, it is the catalytic activity of the topoisomerases that is inhibited.…”
Section: Single Pharmacophore Multiple Targetsmentioning
confidence: 95%
“…As might be expected from the site of resistance mutations, diones are not cross resistant with FQs. In fact, while FQ resistance does not alter susceptibility to diones, resistance to the diones may cause hypersusceptibility to FQs (288). No characterization of toxicity (including selectivity for bacterial over mammalian topoisomerases) of the diones has been reported.…”
Section: Single Pharmacophore Multiple Targetsmentioning
confidence: 99%
“…Only one report describes the differential interaction of an 8-methyl 2,4-dione with Streptococcus pneumoniae gyrase and Topo IV (27). Thus, characterization and comparison of the effectiveness of assorted dione structures against the catalytic activities of S. aureus and E. coli topoisomerases in vitro should provide useful insight into target selection by a dione in vivo.…”
mentioning
confidence: 99%